Sexual Assault and Advance Consent: A Feminist Judgment in R v JA - Koshan, Jennifer (feminists@law, 2015)
This is the audio recording of a seminar given at the Kent Centre for Law, Gender and Sexuality, University of Kent, on 12 November 2015. The paper discusses a draft feminist judgment in R v JA [2011] SCC 28 (Supreme Court of Canada), a spousal sexual assault case involving the issue of whether parties can consent in advance to sexual activity that will occur while they are asleep or unconscious. The JA ruling has generated critique and debate amongst feminists and law and sexuality scholars that pits women's security interests against their sexual autonomy. The judgment endeavours to analyse whether it is possible to adopt an approach to advance consent that advances both of these interests, or whether they are ultimately irreconcilable. In doing so, it explores the proposal of Justice Fish, writing in dissent at the Supreme Court of Canada, that an appropriate balance might be that taken under s 75(2)(d) of the UK's Sexual Offences Act 2003, which creates a presumption against advance consent but not an absolute bar to arguing it. The author is a member of the Women's Court of Canada project, the first feminist judgment re-writing project internationally, and she also speaks to the potential value as well as challenges of feminist judgment writing.